Bond Strength of One-Step Adhesives under Different Substrate Moisture Conditions - Faria-e-Silva, André Luís; Fabião, Mayra Melo; Sfalcin, Ravana Angelini; Meneses, Murilo de Souza; Santos-Filho, Paulo César Freitas; Soares, Paulo Vinícius; Martins, Luís Roberto (European Journal of Dentistry, 2009)
Objectives: The aim of this study was to evaluate the bond strength of one-step adhesive systems to dry or moist dental substrate.Methods: Thirty human third molars were sectioned into two halves, in the mesio-distal direction, parallel to the long axis of the tooth. Each half was embedded in a polystyrene resin cylinder so that the buccal/lingual surface remained exposed. This exposed surface was abraded to obtain both flat exposed enamel and dentin. The samples were randomly allocated according to the adhesive system (Xeno III, Adper Prompt and iBond) and moisture condition (dry and moist). The substrates were air-dried for 30 s for dry condition, while the moist substrates were re-wet with 2.5 µl of distilled water after drying. After the adhesive procedures, two resin composite cylinders were build-up on dentin and enamel substrates, totaling four per sample. A shear load was applied to the samples at a crosshead speed of 0.5 mm/min until failure. Data were statistically analyzed by three-way ANOVA and the Tukey test (α=0.05).Results: The evaluated one-step adhesives showed higher bond strength to dentin than enamel. The iBond presented better bond performance to moist substrate and Xeno III to dry substrate. The moisture condition did not interfere in the performance of Adper Prompt. The Xeno III and iBond presented higher bond strength than the other adhesives to both dry and moist substrates.Conclusions: The moisture condition of substrate interfered in the performance of one-step selfetching adhesives and the best moisture condition was material dependent. (Eur J Dent 2009;3:290-296)
Keywords: Bond strength; One-step adhesives; Moisture; Self-etching adhesives